Event-Triggered H∞Control for Networked Control Systems with Time-Varying Delay. (11th March 2014) - Yan, Huaicheng; Yan, Sheng; Zhang, Hao; Shi, Hongbo
Abstract : This paper deals with H ∞ controller design problem for event-triggered networked control systems (NCSs), where the next task release time and finishing time are predicted based on the sampled states. A new model of NCSs that involves the network conditions, state, and event-triggered communication strategy is proposed. Based on this model, some novel criteria for the asymptotic stability analysis and H ∞ state feedback controller design of the event-triggered NCSs with timevarying delay are established to guarantee a prescribed H ∞ disturbance rejection attenuation level. Finally, a numerical example is provided to illustrate the effectiveness of the proposed method.